2020
DOI: 10.22271/chemi.2020.v8.i2k.8848
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives of grafting in Solanaceous vegetables: A review

Abstract: Vegetables are nutritionally rich, high-valued crops and remunerative enough to replace subsistence farming. However, vegetables especially Solanaceous vegetables are highly sensitive to biotic and sudden irregularities in weather factors at any phase of crop growth can affect the normal growth, flowering, fruit development and subsequently the yield. Grafting in vegetable has emerged as a promising surgical alternative over relatively slow conventional breeding methods aimed at increasing tolerance to biotic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Furthermore, other researchers reported that rootstocks had excellent effects on scion growth. They found that grafting increased nutrients and mineral uptake, tolerance to stresses, synthesis, and translocation of water and plant hormones (Kroggel and Kubota 2017, Noor et al 2019, and Shiwani 2020. It has been documented those rootstocks improved vegetative growth and significantly increased Egypt.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, other researchers reported that rootstocks had excellent effects on scion growth. They found that grafting increased nutrients and mineral uptake, tolerance to stresses, synthesis, and translocation of water and plant hormones (Kroggel and Kubota 2017, Noor et al 2019, and Shiwani 2020. It has been documented those rootstocks improved vegetative growth and significantly increased Egypt.…”
Section: Introductionmentioning
confidence: 99%